2005
DOI: 10.1136/jnnp.2003.032003
|View full text |Cite
|
Sign up to set email alerts
|

Anosmia is very common in the Lewy body variant of Alzheimer's disease

Abstract: Background: Olfactory abnormalities are reported in Alzheimer's disease and Parkinson's disease. Anosmia appears to be common in dementia with Lewy bodies but not in pure Alzheimer's disease. Objective: To determine whether anosmia improves discrimination between the Lewy body variant (LBV) of Alzheimer's disease and ''pure'' Alzheimer's disease. Methods: 106 cases of necropsy confirmed pure Alzheimer's disease (n = 89) or LBV (n = 17) were reviewed. All had received butanol odour threshold testing. Anosmia wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
70
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 34 publications
9
70
1
Order By: Relevance
“…Previous studies using olfactory tests revealed that olfactory dysfunction is more common and marked in DLB than in AD [12,13]. In the present study, approximately 40% of DLB patients had anosmia or hyposmia at the onset of memory loss, while almost none of the AD patients and normal controls did.…”
Section: Discussionmentioning
confidence: 51%
“…Previous studies using olfactory tests revealed that olfactory dysfunction is more common and marked in DLB than in AD [12,13]. In the present study, approximately 40% of DLB patients had anosmia or hyposmia at the onset of memory loss, while almost none of the AD patients and normal controls did.…”
Section: Discussionmentioning
confidence: 51%
“…While olfactory dysfunction has been demonstrated in AD, patients with Lewy body dementia have even greater impairments in olfaction, lending significance to the role of Lewy pathology in olfactory dysfunction [42][43][44] . Based on this assumption, it would be expected that nondegenerative causes of parkinsonism have intact olfaction, as is the case in vascular parkinsonism [45] and MPTP-induced parkinsonism [46] .…”
Section: Olfactory Loss As a Biomarker Of Pdmentioning
confidence: 99%
“…Olfactory loss may also be an important preclinical marker of dementia, especially DLB (Olichney et al, 2005) and Alzheimer's disease. A major advantage of olfactory tests is that they are inexpensive and non-invasive.…”
Section: Olfactionmentioning
confidence: 99%